Development and evaluation of porous membrane pellets of disopyramide phosphate for sustained release - Bathool, Afifa; Gowda, D Vishakante; Khan, Mohammed S (Asian Journal of Pharmaceutics (AJP), 2014)
Aim of the present study was to prepare pellets of disopyramide phosphate (DPP) using blend of Hydroxy Propyl Methyl Cellulose (HPMC K4M) and Avicel PH 101 (Microcrystalline cellulose) and to coat the prepared pellets by mixture of Eudragit L100 and Eudragit S100 to obtain microporous membrane for controlled release. Extrusion/spheronization method was employed to produce spherical discrete pellets of uniform size. Solid, porous, discrete, reproducible pellets were obtained. Sieve analysis data indicated that the size of prepared pellets was in the range of 850 â€“ 1180 Î¼m.Yield of pellets was found to be 96.5%. Prepared pellets were spherical in shape, with pores on the surface, as evidenced by scanning electron microscopy (SEM). Compatibility of the drug after encapsulation in the pellets was confirmed by DSC and by FTIR. The prepared pellets were analyzed quantitatively for the drug content and were found to be 96.2%. In vitro drug release studies indicated F3C2 as optimized formulation. Formulation F3C2 shows 93.26% drug release up to 12 hrs. It was also observed that there was no significant release of drug in gastric pH. The release kinetics for all the formulations indicated that drug release followed non-Fickian diffusion. In vivo study of DPP (300 mg) pellets was carried out in healthy albino rats. Plasma DPP concentrations and other pharmacokinetic parameters were statistically analyzed. The results of paired T-test for the comparison of pharmacokinetic data showed that there was no significant variation between the marketed (NorpaceÂ® CR) and F3C2. The stability studies performed on F3C2 showed no significant difference in drug content. It was concluded that the drug release performance was greatly affected by microporous membrane coating used in the preparation of pellets.